Predicting Financial Distress in Indonesia’s Hospitality Sector: a 2019-2022 Analysis - Amara, Ulfha Suryana; Fadli, Fadli (MBIA, 2024)
This study investigates the most accurate financial distress prediction model for companies within the Hotel, Resort, and cruise lines sub-sector listed on the Indonesia Stock Exchange from 2019 to 2022. The research uses a quantitative descriptive methodology to analyze numerical data derived from each model's parameters. Secondary data, sourced from financial reports available on IDX.co.id or official company websites, forms the basis of analysis. Results indicate that the Zmijewski prediction model outperforms others, achieving a remarkable accuracy level of 100%. In contrast, the Atman and Springate models follow with a 52% accuracy rate, securing the second position. The Grover model ranks third, demonstrating a 50% accuracy level. Lastly, the Taffler model trails behind with a 34.6% accuracy level. In summary, this research provides insights into the effectiveness of various financial distress prediction models within the specified industry and geographical context. The findings underscore the significance of the Zmijewski model as a robust tool for anticipating financial distress among companies in the Hotel, Resort, and cruise Lines sector on the Indonesia Stock Exchange during the stated timeframe. The study's quantitative descriptive approach enhances understanding by presenting numerical evidence, contributing valuable knowledge to financial analysis and risk management practices within the targeted industry sector. Keywords: financial distress, Altman, Springate, Foster, Taffler, Zmijewski, Grover Abstrak Penelitian ini bertujuan untuk meneliti model prediksi kebangkrutan keuangan yang paling efektif bagi perusahaan-perusahaan di sub-sektor Hotel, Resort & Cruise Lines yang terdaftar di Bursa Efek Indonesia dari tahun 2019 hingga 2022. Melalui pendekatan deskriptif kuantitatif, data numerik dari berbagai parameter model dianalisis. Data sekunder dari laporan keuangan yang tersedia di idx.co.id atau situs web resmi perusahaan digunakan sebagai dasar analisis. Hasil penelitian menunjukkan bahwa model prediksi Zmijewski menunjukkan kinerja unggul dengan tingkat akurasi mencapai 100%. Sementara model Atman dan Springate menduduki posisi kedua dengan tingkat akurasi sebesar 52%, diikuti oleh model Grover di posisi ketiga dengan tingkat akurasi 50%. Model Taffler memiliki tingkat akurasi 34,6%. Penelitian ini memberikan wawasan yang signifikan terkait efektivitas model prediksi kebangkrutan keuangan dalam konteks industri dan geografis tertentu. Temuan tersebut menggarisbawahi keandalan model Zmijewski sebagai alat prediksi kebangkrutan keuangan yang handal bagi perusahaan-perusahaan di sub-sektor Hotel, Resort & Cruise Lines di Bursa Efek Indonesia selama periode yang diteliti. Pendekatan deskriptif kuantitatif yang digunakan dalam penelitian ini memberikan kontribusi penting bagi pemahaman tentang praktik analisis keuangan dan manajemen risiko dalam industri yang dituju. Dengan demikian, penelitian ini tidak hanya memberikan gambaran tentang kinerja berbagai model prediksi kebangkrutan keuangan, tetapi juga menyoroti keunggulan model tertentu dalam konteks yang spesifik. Kata kunci: financial distress, Altman, Springate, Foster, Taffler, Zmijewski, Grover